SIFAT MEKANIK BETON DENGAN PEMANFAATAN SERBUK CANGKANG KERANG DAN SERBUK KACA - Sinta Devi, Debby; Fauzi, Marguan; Salsabiela, Tiara (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Economic and infrastructure development continues to increase as a result of global urbanization. Infrastructure development is currently using a lot of concrete material. The production of concrete is problematic as it produces carbon dioxide (CO2) gas by weight from the production of cement. This research aims to evaluate innovative, environmentally friendly alternatives that allow a reduction in the amount of natural resources consumed in the manufacture of concrete. The method used was the experimental method. The concrete mixtures used were cement, 10%, 15% and 20% cockle shell powder, fine aggregate in the form of sand and glass powder with a substitution percentage of 20%, 25% and coarse aggregate in the form of gravel and water. Fresh concrete testing in the form of slump and setting time tests as well as testing the specific gravity and compressive strength of concrete for all variations of waste utilization. The results show that the use of glass powder waste and cockle shell powder with the optimum variation is 10% cockle shell powder and 20% glass powder. The slump test result is 11,5 cm, the final binding time is 205 minutes, the specific gravity is 2496,82 kg/m3 and the compressive strength test value is 31,63 MPa. The use of cockle shell powder and glass powder in concrete mixtures has the potential as a concrete constituent material as a sustainable recycled material. Abstrak Perkembangan ekonomi dan infrastruktur terus meningkat sebagai akibat dari urbanisasi global. Pembangunan infrastruktur saat ini banyak menggunakan material beton. Produksi beton menjadi permasalahan karena menghasilkan gas karbon dioksida (CO2) sebesar berat yang dihasilkan dari produksi semen. Penelitian ini bertujuan untuk mengevaluasi alternatif inovatif, dan ramah lingkungan yang memungkinkan pengurangan jumlah sumber daya alam yang dikonsumsi dalam pembuatan beton. Metode yang digunakan adalah metode eksperimental. Campuran beton yang digunakan adalah semen, serbuk cangkang kerang 10%, 15% dan 20%, agregat halus berupa pasir dan serbuk kaca dengan persentase substitusi 20%, 25% serta agregat kasar berupa kerikil dan air. Pengujian beton segar berupa uji slump dan setting time serta pengujian berat jenis dan kuat tekan beton untuk semua variasi pemanfaatan limbah. Hasil menunjukkan bahwa penggunaan limbah serbuk kaca dan serbuk cangkang kerang dengan variasi optimum adalah 10% serbuk cangkang kerang dan 20% serbuk kaca. Hasil uji slump adalah sebesar 11,5 cm, waktu ikat akhir 205 menit, berat jenis 2496,82 kg/m3 dan nilai uji kuat tekan sebesar 31,63 MPa. Penggunaan serbuk cangkang kerang dan serbuk kaca dalam campuran beton memiliki potensi sebagai bahan penyusun beton sebagai material daur ulang yang berkelanjutan.